Answer:
(x,y) -->(x+4,y+4)
Step-by-step explanation:
The triangle DEF is plotted and shown below:
We can also use the calculation method to find the centroid as done below:
![\begin{gathered} (x,y)=((-1+7+9)/(3),(4-3+5)/(3)) \\ =((15)/(3),(6)/(3)) \\ =(5,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y81i5ouut7b8s9u8z38rxz6w9w8akdvtv1.png)
The centroid of △DEF = (5,2)
If the centroid of △D'E'F' is (9,6)
Then, the translation rule is derived below:
![\begin{gathered} (5+a,2+b)=(9,6) \\ a=4,b=4 \\ \implies(x,y)\to(x+4,y+4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ds55qph0dsy3o7u368an9obxj6hxsrgfmv.png)